Clinical letters to patients with intellectual disabilities after psychiatric review: A quality improvement project. (March 2023) - Sawhney, Indermeet; Zia, Asif; Gates, Bob; Sharma, Anu; Adeniji, Adetayo
Aim: This Quality Improvement Project sought to improve communication between patients with intellectual disabilities and their psychiatrists by sharing medical information using an easy read letter format following psychiatric review. Background: Writing directly to patients is in keeping with good medical practice. Previous studies have shown patients with intellectual disabilities prefer letters tailored to meet their needs. Method: An easy read letter was used by nine psychiatrists who handed them to 100 consecutive patients after review. Feedback of acceptability to patients was obtained using a three-item facial rating scale and the use of free text. Feedback of acceptability was obtained from participating psychiatrists. Results: Patients found the easy read letter helpful and felt it should be used routinely. Psychiatrists felt this approach was beneficial as well as aiding patient understanding of review. Conclusions: The easy read letter was reported to improve communication following psychiatric review. Limitations are acknowledged but it is concluded that an easy read letter should be adopted as routine practice following psychiatric review, for people with intellectual disabilities.